Protective role of polyphenol extract from highland barley against cisplatin-induced renal toxicity and mitochondrial damage in rats - Liu, Yunfan; Zhai, Jiazhou; Qin, Fei; Gao, Liping; She, Yongxin; Wang, Mengqiang (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
The aim of this study was to investigate the protective effect of polyphenol extract from Highland barley (HBPE) on cisplatin (CDDP)-induced oxidative damage and mitochondrial damage in rat kidney. The experimental rats were divided into control group, CDDP group, HBPE (600 mg/kg) group, CDDP+HBPE (150 mg/kg) group, CDDP+HBPE (300 mg/kg) group and CDDP+HBPE (600 mg/kg) group. Rats in each group were intragastrically fed with normal saline and corresponding dose of HBPE for 21 d. On the 16th day, CDDP group and CDDP+HBPE group were injected intraperitoneally with CDDP (7.5 mg/kg), and the other groups were injected with the same amount of normal saline. On the 22nd day, the rats were killed and blood samples were taken to detect the contents of blood urea nitrogen (BUN) and creatinine (CrE) in serum, and calculate the kidney index. The kidney samples were used for the measurement of malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), lactate dehydrogenase (LDH), malate dehydrogenase (MDH), hexokinase (HK), and processed for histopathological examinations. The results showed that HBPE improved the abnormalities of serum CrE, BUN, antioxidant and carbohydrate metabolic enzymes in kidney induced by CDDP. HBPE can also reduce the degeneration of renal tubules and glomerular atrophy. Therefore, HBPE has a significant protective effect on oxidative stress injury and mitochondrial damage induced by CDDP in rats.